Participação política e fé : o papel da igreja na formação das organizações sociais populares : região Alto Uruguai do RS (1974-1990) - Seminotti, Jonas José (2007)
This dissertation consists of an analysis on the role of the progressive sectors of the Catholic Church in the formation of social and popular leaderships and organizations in Alto Uruguai region, among Brazil s redemocratization, between 1974 and 1990. The objective is to understand the factors that had contributed in order to appear detached leaderships and organizations of social and political action in Erechim s Diocese, from the work of the Catholic Church progressive sectors and of its correlate mediation in this period marked by the censorship of the democratic freedoms in the country. We have concentrated our focus on the second half of the 1970 s, for being the beginning of the process for the redemocratization of the country, and all the 1980 decade, for fitting the end of the military system and the political opening and for being the period of the formation of the social popular organizations in Alto Uruguai region. The researched space is Alto Uruguai region - RS, also understood here, as Erechim s Diocese, which is formed by 31 cities, but only Erechim had its population centered in the urban center. The other cities were essentially agricultural, with small agriculturists, who lived in interior communities and for its religious spirit and communitarian participation, had adhered to the changes proposals by the progressive sectors of the Church, from Vatican Council II and from the Medellín and Puebla Conferences. For better understanding of the process that it develops on national and regional level, we have organized the work in three chapters. The first one approaches the Brazilian context, from the military blow to the redemocratization, showing how the military governments had worked in the political plan, the repression period and, simultaneously, the slow and gradual phase of political opening; also we have approached the performance of the contrary organizations of the civil society to the system, the fight for the redemocratization and for the rights conquest. The second chapter analyzes the performance of the progressive sectors of the Catholic Church in Alto Uruguai region, the groups Esquema II and Paulo VI, the formation process of the Diocesan Servers School, of the Youth Pastoral and the Labor Pastoral, from where appears innumerable leaderships of social and political action, especially among the young agriculturists; and the internal conflicts between the progressive and conservatives sectors of the Catholic Church in the Diocese. The third chapter presents, from the national context and from the performance of the progressive sectors of the Church, how the social popular organizations in Alto Uruguai region are formed, among them, we have the urban and agricultural unions (CUT), the Regional Commission of Reached by Barrages (CRAB), the Rural Worker Women Movement (MMTR), the Popular Education Center (CEPO) and the Worker Union (PT). Beyond this study, we hope to contribute for a better understanding of the conjunctural factors that had contributed for the redemocratization of the country, but especially to make a deeper analysis on the formation of the actors of social and political action in Alto Uruguai region, consequence of the democratic deepening and the new social political context of the country